Öğrencilerin grafik okuma ve oluşturma becerilerinin fonksiyonel anladmda incelenmesi - Egin, Mustafa (My University, 2010)
VIEWS OF SOCIAL STUDIES TEACHERS ON THE EUROPEAN UNION This study aims to examine the views of Social Studies teacher candidates on the political, socio-economic, educational, human rights related, democratic, and economic dimensions of the Turkish-EU relations. The study uses survey methodology. The questionnaire used to gather the data was developed after the existing literature was reviewed. Following the preparation of the questionnaire, it was applied, as part of the study, in Atatürk, Kafkas, Marmara and Mehmet Akif Ersoy Universities. The sample for the study consisted of the freshmen and senior students majoring in Social Studies Teaching in these universities. Certain analyses were conducted upon the collection of the data. In this context, views the of teacher candidates on the political, socio-economic, human rights related, democratic, and economic dimensions of the Turkish-EU relations were subjected to a detailed analysis. Key Words: Social Studies, European Union.

THE RESEARCH OF STUDENTS’ ABİLİTİES ABOUT READİNG AND CREATİNG GRAPHS İN THE MEANİNG OF FUNCTİON In this research, students’ knowledge about function graphs and interpretting skills are considered. The answers given by the students to the questions which they had never seen before, thet’s why they do not comply with didactic contracts, are analyzed, then various estimations are formed about knowledge about function graphs and interpretting skills by these answers. Since the group is researched deeply, the research is a case study. The group consists of 120 12th grade students from two state schools in Istanbul and 30 5th grade preservice maths teachers. First of all, a questionnaire is used in order to understand their knowledge about function graphs and interpretting skills.The questions are inspired by the questions used in Bloch’s (2000) doctorate study. The answers given to the questionnaire are seperated into subcategories. In this process, three different maths education experts’ opinions are received to make subcategories. Then one or two students from each subcategories have semi-structured interview. The aim is to get their thought about their answers and to explore their mental thought structures in this process. Lastly, the questionnaire is used to preservice teachers and their attitudes about this subject are investigated. According to the results, students are not good enough at function graphs and interpretting skills. Students do not have problem in the activities related to graphs in classes.But if some variables are changed, serious problems appear. This situation shows that students learn the methods suitable for the questions shown and they can easily use these ones whenever they need; but they cannot use new methods in different questions related to the same concepts. While some students try to modify the methods to the new situations, some students directly use the same methods.It is remarkable that many students cannot give any answer or comment to these questions.As a result, students learn (or memorize) methods instead of conceptual learning and this learning does not contribute to their conceptual learnings.Moreover, it is found out that students have misconceptions in the process of reading and creating graph and especially they use transitions between representations because of their habits instead of creating a solution. As a result of this research, it is necessary to pay much attention to activities of transformation between function representations and to support these activities by technology. KEY WORDS: Function Concept, Didactic Contract, Multiple Representations, Misconceptions
Keywords: Orta Öğretim; Ortaöğretim; Öğrenim ve Öğretim_Matematik